Treaties, trenches, mud, and blood - Hale, Nathan, 1976- (Hale, Nathan, 1976- Nathan Hale's hazardous tales., 2014)
Presents a graphic novel story in which Nathan Hale takes readers to the twentieth century where he explains the origins, key players, battles, and impact of World War I.